2016
DOI: 10.1177/0009922815623230
|View full text |Cite
|
Sign up to set email alerts
|

A Healthy Weight for Toddlers? Two-Year Follow-up of a Randomized Controlled Trial of Group Well-Child Care

Abstract: Rapid weight gain during the first year of life is associated with childhood obesity, adult obesity, and all its concomitant morbidities. 1,2 Over the past 30 years, obesity among children 2 to 5 years old doubled. 3 As pediatric health care providers interact with young families routinely throughout the first few years of life, they may be in an ideal position to influence the rate of weight gain.Innovations in care are needed: although past interventions have demonstrated that intensive anticipatory guidance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 15 publications
(21 reference statements)
0
23
0
Order By: Relevance
“…The experimental arm received infant well care (over the first year of life) focused on maternal–infant attachment and PSE in a group setting with other mothers and infants. In this sample, no statistically significant differences were observed between groups regarding dietary practices or child weight up to 36 months of age; however, the experimental group had less incidence of ever being overweight (Shah et al, 2016). A limitation of the study was that PSE of the mothers was not measured; therefore, differences between groups could not be examined nor pre-/post-intervention differences.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…The experimental arm received infant well care (over the first year of life) focused on maternal–infant attachment and PSE in a group setting with other mothers and infants. In this sample, no statistically significant differences were observed between groups regarding dietary practices or child weight up to 36 months of age; however, the experimental group had less incidence of ever being overweight (Shah et al, 2016). A limitation of the study was that PSE of the mothers was not measured; therefore, differences between groups could not be examined nor pre-/post-intervention differences.…”
Section: Resultsmentioning
confidence: 57%
“…Shah and colleagues (2016) conducted an intervention study that examined whether dietary behaviors and/or infant/toddler weight differed in a group of mother–infant dyads who received infant well care in a group setting (experimental) versus an individual setting (control). The experimental arm received infant well care (over the first year of life) focused on maternal–infant attachment and PSE in a group setting with other mothers and infants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After duplicate removal, and title and abstract screening, 230 references were selected for full‐text review. One hundred and eighty eligible studies were identified, describing 39 trials, comprising 46 interventions . Five trials had more than one eligible intervention arm .…”
Section: Resultsmentioning
confidence: 99%
“…13 Group visits (also known as shared medical appointment) models for ADHD chronic care management can offer support to families but the acceptability of this model for medical providers and families, is not yet known. 14 While group visit models have been examined for well child visits and other pediatric chronic diseases, such as asthma and diabetes, [15][16][17][18][19][20] they have yet to become part of mainstream practice.…”
Section: Introductionmentioning
confidence: 99%